2022
DOI: 10.3389/fonc.2022.851864
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Rapid Daratumumab Infusion: A Retrospective, Multicenter, Real-Life Analysis on 134 Patients With Multiple Myeloma

Abstract: BackgroundThe anti-CD38 monoclonal antibody daratumumab is the backbone of most anti-multiple myeloma (MM) regimens. To mitigate the risk of infusion-related reactions (IRRs), intravenous daratumumab administration requires 7 hours for the first infusion and 3.5-4 hours thereafter, thus making daratumumab-containing regimens burdensome for patients and health care resources. Preliminary data suggest that a rapid (90-minute) infusion of daratumumab is safe and does not increase IRRs. The rapid schedule was adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…An important issue in the use of daratumumab is the speed of infusion. Indeed, there is RW evidence that a rapid daratumumab infusion protocol did not increase the rate of AEs, as compared with the standard infusion protocol ( 85 , 86 ).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…An important issue in the use of daratumumab is the speed of infusion. Indeed, there is RW evidence that a rapid daratumumab infusion protocol did not increase the rate of AEs, as compared with the standard infusion protocol ( 85 , 86 ).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Drugs targeting the surface proteins of plasma cells constitute yet another therapeutic option. On this basis, various monoclonal antibodies against the glycoprotein CD38 expressed in Ig-secreting plasma cells and thymocytes [ 68 , 69 ] are now being studied for MG. Mezagitamab was recently evaluated in a randomized phase 2 trial, although the results have yet to be published [ 70 ]. Another anti-CD38 antibody, daratumumab, has been evaluated in a retrospective, single-centre case series of seven patients with autoantibody-driven neurological autoimmune diseases, including one patient with MG.…”
Section: New Therapeutic Strategies In Myasthenia Gravismentioning
confidence: 99%
“…To decrease infusion times, numerous trials have confirmed that rapid infusion of daratumumab 90 min and isatuximab 70 min can be initiated safely following evidence of tolerability during the first cycle ( Table 3 ). 23 29 …”
Section: Fda-approved Next-generation Therapeuticsmentioning
confidence: 99%
“…To decrease infusion times, numerous trials have confirmed that rapid infusion of daratumumab 90 min and isatuximab 70 min can be initiated safely following evidence of tolerability during the first cycle (Table 3). [23][24][25][26][27][28][29] Infusion-related reactions (IRRs) are common in all formulations but more likely with IV administration and occur primarily with the first dose (Table 3). Associated symptoms are generally low grade and include chills, fever, nausea, nasal congestion, cough, and dyspnea.…”
Section: Fda-approved Next-generation Therapeuticsmentioning
confidence: 99%